PHARMACOLOGICAL BASIS FOR THE CONTINUAL USE OF THE ROOT OF SENNA SIAMEA IN TRADITIONAL MEDICINE - OTIMENYIN S. O.; KOLAWOLE; J. A.; M. NWOSU (International Journal of Pharma and Bio Sciences, 2010)
The sub-acute toxicity of the aqueous extract of the root of Senna siamea was studied in rats. Oral administration of S. siame for 28 days produced neither mortality nor changes in behavior or any physiological activities. Results obtained showed that the extract insignificantly (p>0.05) affected the mean body and organ weight of wistar rats. Hematological parameters (PCV, Hb, WBC. and RBC) and biochemical parameters, (Serum creatinine, serum urea, sodium, potassium ions, alkaline phosphatase (ALP), alanine aminotransaminase (ALAT), aspartate aminotransaminase (ASAT)) were not affected by the extract. Histological studies of vital organs did not show any statistical significant difference between the same organs. These results may explain the continual use of S. siamea in folk medicine.